2013
DOI: 10.5430/cns.v2n1p64
|View full text |Cite
|
Sign up to set email alerts
|

Women with breast cancer: Embracing and distancing themselves from the term cancer survivor

Abstract: The purpose of this study was to examine the lived experiences of women who had been diagnosed with breast cancer, specifically focusing on the meaning they associate with the term cancer survivor. A woman who has been diagnosed with breast cancer in North America undoubtedly will encounter the term cancer survivor at some point following her diagnosis. However, few studies have been focused on examining the meaning of this term for women who have been diagnosed with breast cancer, let alone whether these wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It has been suggested that overuse of the survivor label may present a barrier to seeking help for ongoing physical and emotional issues (Little et al., ; McKenzie & Crouch, ; Pertl, Quigley, & Hevey, ; Stephenson et al., ). This research has illustrated this very point, as some of the young women in the study felt constrained by expectations of the survivor role so that they were unable to share their ongoing physical and emotional problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that overuse of the survivor label may present a barrier to seeking help for ongoing physical and emotional issues (Little et al., ; McKenzie & Crouch, ; Pertl, Quigley, & Hevey, ; Stephenson et al., ). This research has illustrated this very point, as some of the young women in the study felt constrained by expectations of the survivor role so that they were unable to share their ongoing physical and emotional problems.…”
Section: Discussionmentioning
confidence: 99%
“…A body of research has emerged exploring how individuals who have had cancer perceive the term survivor (e.g. Davis, Myers, Nyamathi, Lewis, and Brecht (); Documet, Trauth, Key, Flatt, and Jernigan (); Kaiser (); Morris, Campbell, Dwyer, Dunn, and Chambers (); Stephenson, Fletcher, and Schneider ()). This work has identified that whilst some individuals do embrace the term, many do not feel it resonates with their experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation